Numerical simulation of low Reynolds number flows over two circular cylinders in tandem - Didier, E. (2009)
Flow interference between two circular cylinders, with same diameter D, in tandem arrangement is investigated numerically using a fully coupled resolution method. Numerical simulations are performed for Reynolds number Re=200, with centre-to-centre cylinder distance L varying from 1.5 to 10D. The two-dimensional Navier-Stokes equations are written in integral form and discretized by the finite volume method for unstructured grids. Equations are solved using an original fully coupled resolution method, without any transformation of continuity equation, that allows obtaining simultaneously velocity and pressure fields. Results analysis shows that change in flow topology occurs at L=4D and manifests by a large jump on mean and fluctuating forces and Strouhal number. Similar trend is observed for present results at Re=200 and that obtained in a previous study at Re=100. It is show that maximum lift force is reached when vortex shedding of the two cylinders is in-phase and that forces acting on each cylinder are influenced by the phase lag of fluctuating lift between the two cylinders.